Pengaruh Pemahaman Risiko Audit dan Ekspektasi Penghargaan Finansial terhadap Minat Mahasiswa Berkarir sebagai Auditor Eksternal - Arif Nadzirul Haq; Bella Putrie Nindyawan; Novira Fazri Nanda (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2026)
The growth of accounting graduates in Indonesia has not been accompanied by a proportional increase in the number of public accountants, driven by students' low interest in pursuing a career as an external auditor in Public Accounting Firms (KAP). This study aims to examine the effect of audit risk understanding and financial reward expectations on accounting students' career intentions as external auditors. This research is explanatory quantitative in nature, employing a survey method. Data collection was conducted using a Likert-scale questionnaire distributed via Google Forms to 50 accounting students selected through purposive sampling. Data analysis techniques included classical assumption tests and multiple linear regression analysis, executed using SPSS software. The results demonstrate that audit risk understanding and financial reward expectations, both partially and simultaneously, have a positive and significant effect on career intentions as an external auditor.